Analisis Klinis Hidung Penderita Sindrom Down pada Suku Minangkabau - Muhammad Afif Furqan; Yuniar Lestari; Dolly Irvandy; Arni Amir; Indra Ihsan (Oto Rhino Laryngologica Indonesiana, 2023)
Background: Down's syndrome (DS) is a congenital disorder due to prenatal trisomy 21 which causes malformations of organs and body shape, including the nose. The variables measured are the points that determine the aesthetics of the nose. Purpose: This study aimed to describe primary data thus obtained from nose anthropometry of Down syndrome in the Minangkabau tribe can be used as a reference in nose reconstruction in patients with Down syndrome to restore physiological function and add aesthetic value. Methods: This research is a descriptive type study with a cross-sectional method using primary data as subjects. The sample of this study were people with Down syndrome who have Minangkabau ethnicity, totaling 22 samples with an age range of 13-25 years from special schools in Padang city. The study was conducted by observation and anthropometry of the nose using graphical images computerized by software called rhinobase software. Results: The results of this study showed that the nose width is 15.25 mm ± 2.07, the ala nasi width is 41.41 mm ± 3.47, the nasofrontal angle was 133.59° ± 5.89, the nasolabial angle was 109.24° ± 13.60 , the nose length is 32.16 mm ± 3.24. Conclusion: From this study, various results were found on the size of the aesthetic points of the nose of Down syndrome patients in the Minangkabau ethnic group when compared to DS patients in different race, ethnic, or non DS patients.